The Use of NeuroLinguistic Programming in the Teaching of Writing - Makmun, Nadiah (ENCOUNTER, 2012)
Writing is an important skill in English that has to be learned by the students beside the other language skills. The students of non English department especially have difficulty to do writing in English. They do not only have lack of vocabularies in English, but also low motivation to do writing skill. NLP (NeuroLinguistic Programming) in English learning process can be used to help and motivate the students become aware at a feeling level of doing writing through game of using picture. NLP is a collection of techniques, patterns, and strategies for assisting effective communication, personal growth and change, and learning (Revell and Norman). By using NLP in teaching English makes the students be active learner. Most teachers still use traditional method to teach English, namely by using the lecture method. Most of them just still use the method of GTM to teach English. The tendency of teachers who use such methods usually use TCL (Teacher Centered Learning) not SCL (Student Centered Learning). As a good teacher must create the class more interesting, enjoying and fun. He should use various techniques / approaches to make his class interesting and the students active in the English class. Through NLP, in order that the students will not be passive learners and they can enhance their language skill such as writing.